Analisis Status Depresi Sebagai Faktor Penyebab Hipertensi Berbasis Gender di Indonesia (Studi Indonesian Family Life Survey 5) - Mandagi, Ayik Mirayanti; Ulfa, Itsna Faizah; Yuda Prayogi, Ahmad Rido'i; Pratama, Rochmad Ardiansyah; Azalia Adnin, Arini Banowati; Nur Aisyiyah, Fiko Aninun; Katmawanti, Septa (citeus, 2022)
Depression and hypertension are common and dangerous conditions among the Indonesian population. Measurement of blood pressure and detection of depression need to be done regularly to minimize the impact that occurs in the future. This study aims to determine whether depression is the cause of the incidence of hypertension by gender in Indonesia. The research design used in this study was analytic observation. This study used a cross sectional design, survey with stratified random sampling technique. The data in this study used secondary data based on the results of the Indonesian Family Life Survey Five (IFLS Five) research. Data analysis used a linear regression test. The results showed that there was a relationship between depression status and hypertension in men aged 15-64 years. The relationship between depression status and the prevalence of hypertension in women aged 15-64 years is a significant relationship. The comparison of the prevalence of depression between men and women is that men are more than women by 3.6 percent with an OR of 0.84. The relationship between depression and hypertension in women and men aged 15–64 years in Indonesia is a significant relationship.